THE EFFECT OF LEARNING STYLE ON MATHEMATICS LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS - Nanda Nurohmah; Yudhie Suchyadi; Yuli Mulyawati (Journal of Social Studies, Arts and Humanities (JSSAH), 2022)
Effect of learning style on mathematics learning outcomes. Educational Program for Primary School Teachers of the Faculty of Teacher and Education, University of Pakuan Bogor 2021. This research is a quantitative research of the causal approach. This study aims to withdrive the influence of learning styles on grade V mathematics learning outcomes of Sukaharja District Elementary School 01 Cijeruk District, Bogor Regency. The population of this study was 74 students with 42 samples. This research was conducted by the odd semester of the school year 2021/2022. Based on the results of the analysis obtained a path coefficient (RXY) 0.4264 in the pattern Å· = 1.7934 + 0.102 (x) which means the level of influence in this study is classified as moderate. The influence of learning styles on mathematics learning outcomes is equipped by nutmeg coefficient of determination (RÂ²) 0.1818 or 18.18% and the remaining 81.82% is influenced by factors. The calculation of testing hypotheses produces tcount 2.996 ttable 2131 with a real level of 0.05 so it can be concluded that there is a positive and significant influence between learning styles of the findings of mathematics learning in class V of Sukaharja District Elementary School 01 Cijeruk